Exploring the pros and cons of online courses for physiotherapists — a theoretical study - Lukács, Andrea; Simon, Nóra; Kiss-Kondás, Dóra; Szabó, Tünde Lebenszkyné; Bak, Mehtap Kiklicoz; Bibro, Marta; Göz, Büşra; Bicki, Demet; Akar, Fatma Dilara; Sancaktar, Sabiha İrem; Pehlivan, Sevgi; Gniewek, Teresa; et al. (Health Promotion & Physical Activity, 2023)
Physiotherapy, as a constantly evolving discipline, requires professionals to continually update their knowledge base to enhance patient care. To facilitate this growth, lifelong learning through supplementary educational courses plays a crucial role. The flexible online education has opened new opportunities for adult learners, including physiotherapists, to pursue further education while managing their daily commitments. This paper examines the conceptual framework of online learning in the context of physiotherapy education. It explores the advantages and disadvantages of online courses compared to traditional classroom methods. Online education is classified into three primary types: synchronous, asynchronous, and blended or hybrid courses. Synchronous courses involve real-time interaction with teachers, while asynchronous courses allow learners to access materials at their own convenience. Blended or hybrid courses combine online learning with face-to-face instruction. Advantages of online courses include accessibility, flexibility, cost-effectiveness, diverse learning resources, and the opportunity to build a global professional network. On the other hand, online courses lack continuous communication and interaction between teachers and learners, potentially hindering the learning experience. Learners must possess strong digital skills and self-study capabilities to succeed in online education. The study concludes that the choice between traditional and online education depends on specific course objectives and participant expectations. Regardless of the mode of education, the active participation and engagement of learners are crucial for professional success. As the field of physiotherapy education continues to evolve, ongoing research and innovation are vital to improve the overall learning experience and ensure optimal outcomes for lifelong learners in the healthcare field.